Pembuktian Perbuatan Melawan Hukum dalam Sengketa Pengalihan Hak atas Tanah Ditinjau dari Kebenaran Formil dan Kebenaran Materiil : Studi Putusan Mahkamah Agung RI Nomor 3808 K/Pdt/2024 - Veronika Debby Nonibenia Gulo; hasim purba; Sutiarnoto (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study examines a dispute concerning the transfer of land rights as addressed in Supreme Court Decision Number 3808 K/Pdt/2024, where formal documents, including the Deed of Sale and Purchase and land certificate, indicated a valid transfer of rights, while one party alleged that the transaction did not reflect the actual material circumstances. The research focuses on the proof of unlawful act elements, the validity of the Certificate of Ownership transferred to a good-faith purchaser and judicial considerations in assessing formal and substantive truth. Using a normative juridical method, the study finds that the plaintiff failed to sufficiently prove both the legal basis of ownership and the elements of an unlawful act, resulting in the dismissal of the claim. The Certificate of Ownership remains legally valid and possesses strong evidentiary value as long as it is obtained through lawful procedures.